2019
DOI: 10.21763/tjfmpc.651461
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Participation in Mammography Screening Program and Health Literacy

Abstract: Background/Aim: Breast cancer is the most common type of cancer in women around the world. This study aimed to determine the factors that affect participation in a mammography screening program, and analyze the effect of health literacy on women's level of participation in this program.Methods: The study was planned as a case-control study. Women aged 40-69 years were included in the study. The cases consisted of women who had never participated in the mammography screening program before, and controls consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…20 So family physicians working in Turkey may also encounter women with low levels of education while "health literacy status" of the women also have an adjuvant effect on promoting health. 3 Only 3.40% of the women who were participated in our study were in regular employment (gaining salary from social insurance cover). This "work status" may be employed as casual agriculture workers in addition to their domestic work, but these jobs were not covered by social insurance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 So family physicians working in Turkey may also encounter women with low levels of education while "health literacy status" of the women also have an adjuvant effect on promoting health. 3 Only 3.40% of the women who were participated in our study were in regular employment (gaining salary from social insurance cover). This "work status" may be employed as casual agriculture workers in addition to their domestic work, but these jobs were not covered by social insurance.…”
Section: Discussionmentioning
confidence: 98%
“…1 The Cancer Statistics have still reported breast cancer as the first of all the cancers for the females as a new case while the second reason of death. 2,3 In Turkey, one of the four women have breast cancer. 4 In women receiving a breast cancer diagnosis, 5-year survival rates, according to all the stages, were reported as 83% in developed countries and 53% in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that health literacy level of employed ones may be higher. However, the mean age of the participants in those studies was frequently at middle age level [21][22][23] . When the results of the present study were compared with those studies, it was observed that the participants in the present study were younger (25.32±8.15 years).…”
Section: Discussionmentioning
confidence: 99%